2015
DOI: 10.3389/fpls.2015.00213
|View full text |Cite|
|
Sign up to set email alerts
|

Heat stress during seed filling interferes with sulfur restriction on grain composition and seed germination in oilseed rape (Brassica napus L.)

Abstract: In coming decades, increasing temperatures are expected to impact crop yield and seed quality. To develop low input systems, the effects of temperature and sulfur (S) nutrition in oilseed rape, a high S demanding crop, need to be jointly considered. In this study, we investigated the effects of temperatures [High Temperature (HT), 33°C/day, 19°C/night vs. Control Temperature (Ctrl T), 20°C/day, 15°C/day] and S supply [High S (HS), 500 μm SO2−4 vs. Low S (LS), 8.7 μM SO2−4] during seed filling on (i) yield comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 63 publications
6
55
3
Order By: Relevance
“…4, exogenous NaHS could lead to significant accumulation of soluble sugar under heat stress conditions. The result is consistent with the results of previous studies (Gomathi et al 2013;Brunel-Muguet et al 2015). The positive modulation of exogenous H 2 S donor (NaHS) in sol-uble sugar accumulation might also contribute to enhanced stress tolerance.…”
Section: Discussionsupporting
confidence: 92%
“…4, exogenous NaHS could lead to significant accumulation of soluble sugar under heat stress conditions. The result is consistent with the results of previous studies (Gomathi et al 2013;Brunel-Muguet et al 2015). The positive modulation of exogenous H 2 S donor (NaHS) in sol-uble sugar accumulation might also contribute to enhanced stress tolerance.…”
Section: Discussionsupporting
confidence: 92%
“…The possible reason is that allelochemicals with selectivity and specificities which come from same kind of humus soil can effect seed germination of different medicinal materials and from different kinds of humus soil can effect seed germination of same medicinal material (Yang et al, 2005;Ma et al, 2006), which was supported by the findings of Guo et al (2010) who stated that the leaf water extracts from A. fruticosa show allelopathic inhibition effect on the seed germination and seedling growth of soybean and fababean. And also allelochemicals affected seed cell membrane permeability, cell division and differentiation, respiration, protein synthesis, gene expression, and hormone synthesis and equilibrium (Brunel-Muguet et al, 2015). Nevertheless, in this study, the humus soil from C. korshinskii inhibited the seed germination of Glycyrrhiza uralensis, which is not in line with the findings of Sun et al (2008), who reported that C. korshinskii roots leaf water extract caused significantly inhibition on the seed germination of Glycyrrhiza uralensis.…”
Section: Discussioncontrasting
confidence: 55%
“…Finally, the positive repercussion of an adequate fertilization ameliorating climatic change effects on seed filling should be considered. Thus, it has been shown in oilseed rape that the control of S fertilization under heat stress improved grain quality and reduced the detrimental effects of climate change [56].…”
Section: Importance Of Soil Nutrients In Seed Germination Developmenmentioning
confidence: 99%